On the heterogeneity of depression in Parkinson’s disease - M. R. Nodel; N. N. Yakhno (Неврология, нейропсихиатрия, психосоматика)
Depression in Parkinson’s disease (PD) is one of the leading manifestations of the disease, which reduces quality of life in patients.Objective: to compare the clinical features of depression at different stages of PD.Patients and methods. Examinations were made in 162 PD patients aged 62.14±1.99 years without dementia (PD duration, 5.78±0.58 years; Stage, 2.5±0.6). The Unified PD Rating Scale (UPDRS), the Beck Depression Inventory (BDI), and the Spielberger Inventory, the 16-Item PD Fatigue Scale (PFS-16), and the Starkstein Apathy Scale were examined. Dopaminergic agents (DAAs) were prescribed when movement disorders were insufficiently corrected. Antidepressants were not used during the investigation. The follow-up period was 18 months.Results and discussion. Depression was detected in 136 (84%) patients. Depression symptoms appeared in 16 (12%) patients within 1–8 years before the onset of motor symptoms (MS), in 37 (27%) in the first 2 years after the onset of MS, in 44 (32%) at Hoehn–Yahr stages 2–3 without motor fluctuations (MFs), and in 39 (29%) at the onset of MF. The most severity of depression was noted in cases of its development at the premotor stage and in the period of MF occurrence. During the follow-up, the manifestations of depression disappeared in 16% of the patients taking a DAA; these were relapsing-remitting in 9%, progressive in 11%, or remained stable in 64%. The patients with depression occurring at the premotor stage had a progressive course of depression and a low DAA efficacy: an increase in severity in 30% of cases despite therapy and a reversal in only 10% of cases (versus 25–45% of those at depression onset in the presence of MS). In cases of depression occurring in the first 2 years after MS onset, its reversal was observed in 45%; the group of patients with depression onset in the presence of MF showed a stable course with slight severity fluctuations in 77.8%.Conclusion. Depression in PD is a heterogeneous affective disorder. There is a relatively favorable course of depression when the latter occurs in the first two years of MS onset. Along with DAA inefficacy, the more severity of depression is noted when the latter occurs in the premotor phase of PD and at the stage of MF.